Thoracic Aortic Injury: Embolization of the Tenth Intercostal Artery and Endovascular Treatment in a Young Woman after Posterior Spinal Instrumentation - Konstantinos Lagios; Georgios Karaolanis; Theodossios Perdikides; Theodoros Bazinas; Nikolaos Kouris; Spiros Sfikas; Odysseas Paxinos (Case Reports in Vascular Medicine)
Iatrogenic aortic injuries are rare and well-recognized complications of a variety of procedures, including spinal surgery. The placement of pedicle screws is sometimes associated with devastating consequences. Aortic perforation with rapid hematoma formation and delayed aortic trauma leading to pseudoaneurysm formation have been described in the literature. A case describing a significant time interval between iatrogenic aortic injury and diagnosis in the absence of pseudoaneurysm formation is described in this paper and, according to our knowledge, is unique in the literature. The aortic injury was successfully treated, selecting the appropriate graft and, as a consequence, normal spinal cord blood flow was achieved.